2011
DOI: 10.1901/jaba.2011.44-121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pedestrian Prompts on Motorist Yielding at Crosswalks

Abstract: Pedestrian safety is a serious concern at busy intersections and pedestrian campuses across the nation. Although crosswalks and signs inform pedestrians where to cross, there is no standard protocol for pedestrians to signal drivers that they wish to use the crosswalks, except to stand in or at the crosswalk. We examined the effects of two pedestrian prompts, a raised hand and extended arm, on motorist yielding at uncontrolled crosswalks. The two prompts were effective at increasing yielding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 5 publications
2
53
0
Order By: Relevance
“…Without eye contact, about 55% of the drivers did not stop for the pedestrian, while about 68% of the drivers stopped when the pedestrian was seeking eye contact. A positive effect of pedestrians’ eye contact and/or other gestures (e.g., hand waving, leg movements, and smile) is also demonstrated in terms of increased time to collision and decreased severe braking by drivers (Ren et al, 2016), and increased drivers’ yielding behavior (Nasar, 2003; Crowley-Koch et al, 2011; Zhuang and Wu, 2014; Guéguen et al, 2016). Schmidt and Färber (2009) showed that participants were unable to correctly evaluate pedestrians’ crossing intentions based only on their trajectories, suggesting that parameters of body language are valuable cues.…”
Section: Introductionmentioning
confidence: 95%
“…Without eye contact, about 55% of the drivers did not stop for the pedestrian, while about 68% of the drivers stopped when the pedestrian was seeking eye contact. A positive effect of pedestrians’ eye contact and/or other gestures (e.g., hand waving, leg movements, and smile) is also demonstrated in terms of increased time to collision and decreased severe braking by drivers (Ren et al, 2016), and increased drivers’ yielding behavior (Nasar, 2003; Crowley-Koch et al, 2011; Zhuang and Wu, 2014; Guéguen et al, 2016). Schmidt and Färber (2009) showed that participants were unable to correctly evaluate pedestrians’ crossing intentions based only on their trajectories, suggesting that parameters of body language are valuable cues.…”
Section: Introductionmentioning
confidence: 95%
“…This intervention could also be combined with other effective interventions. Similar to Crowley-Koch et al (2011), combining a gateway configuration of signs with prompts for pedestrians to signal their intent to cross could further increase yielding percentages. This approach may seem more equitable as the prompts are given to both parties involved in the interaction (i.e., both the pedestrian and the motorist are being asked to do something).…”
Section: Figure 10mentioning
confidence: 99%
“…In September of 1997 the government organized an educative campaign called "Give a Life Signal" with the purpose to establish walking the crosswalk even more safe; pedestrians should make a signal with the arm (Crowley-Koch, Van Houten, & Lim, 2011;Van Houten, Malenfant, and Rolider, 1985) before crossing the street so that they would be more visible for the drivers. A theater group made performances in the streets showing how to walk the crosswalk correctly.…”
Section: Maintenance Of a New Cultural Practicementioning
confidence: 99%